2018
DOI: 10.1155/2018/9375910
|View full text |Cite
|
Sign up to set email alerts
|

Case Report of Subanesthetic Intravenous Ketamine Infusion for the Treatment of Neuropathic Pain and Depression with Suicidal Features in a Pediatric Patient

Abstract: Chronic neuropathic pain and depression are often comorbid. Ketamine has been used to treat refractory pain. There is emerging evidence for use in depression. We present a case of a pediatric patient who was successfully treated with subanesthetic intravenous ketamine infusion for chronic neuropathic pain and suicidality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 17 publications
(21 reference statements)
2
14
0
Order By: Relevance
“…Besides its effect on the somatosensory component of chronic pain, here we showed that a single injection of ketamine at a sub-anesthetic dose is sufficient to relieve neuropathic pain-induced depressive-like behaviors for at least 72 h, well beyond the acute pharmacological effects (elimination t1/2 ~10-15 min). The current study is the first to use a mouse model of comorbid neuropathic pain and depressive-like behaviors to show the antidepressant-like effect of acute ketamine administration, which has previously been shown only in rats (Wang et al, 2011) and in some clinical case studies (Bigman et al, 2017;Weber et al, 2018). These results are also in accordance with previous data from stress-related rodent models of depressive-like behaviors (Autry et al, 2011;Li et al, 2010) and human patients with major depressive disorder (Ballard et al, 2014;Berman et al, 2000;Zarate et al, 2006) showing that ketamine is a rapid-acting, long-lasting antidepressant agent whose therapeutic effects are manifested within hours and sustain for several days.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Besides its effect on the somatosensory component of chronic pain, here we showed that a single injection of ketamine at a sub-anesthetic dose is sufficient to relieve neuropathic pain-induced depressive-like behaviors for at least 72 h, well beyond the acute pharmacological effects (elimination t1/2 ~10-15 min). The current study is the first to use a mouse model of comorbid neuropathic pain and depressive-like behaviors to show the antidepressant-like effect of acute ketamine administration, which has previously been shown only in rats (Wang et al, 2011) and in some clinical case studies (Bigman et al, 2017;Weber et al, 2018). These results are also in accordance with previous data from stress-related rodent models of depressive-like behaviors (Autry et al, 2011;Li et al, 2010) and human patients with major depressive disorder (Ballard et al, 2014;Berman et al, 2000;Zarate et al, 2006) showing that ketamine is a rapid-acting, long-lasting antidepressant agent whose therapeutic effects are manifested within hours and sustain for several days.…”
Section: Discussionmentioning
confidence: 80%
“…While our results suggest that upregulated MKP-1 contributes to increased dephosphorylation of ERK, which, in turn, fosters the development of depression, the relationship of MKP-1 and ERK does not seem to follow a linear direction, and this pattern of altered expression does not always seem to be the case. In fact, some previous studies show that both chronic stress and neuropathic pain are associated with an increase in ERK activation in the ACC (Kuipers et al, 2003;Wei and Zhuo, 2008), and that this activation contributes to the induction of affective pain, including aversion in response to painful stimuli (Cao et al, 2009;Dai et al, 2011). Additionally, by combining chronic constriction injury and chronic mild stress, Bravo et al (Bravo et al, 2012) showed that rats with comorbid chronic pain and depressive-like behaviors show a robust increase of ERK in the ACC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study bring an evidence of a limitation of ketamine administration as a COS animal model (perhaps for schizophrenia animal models in general) because it induces sex‐dependent differences in the behavior of prepubertal rats, which may not be involved in COS (Weisinger et al, 2013; Ordóñez et al, 2016). Notwithstanding incongruence with COS, such sexual differences in ketamine effects (and NMDA receptor) are indeed involved in several psychiatric conditions, like depression; hence, the present results may contribute with future researches with ketamine as an adjunctive therapy in childhood depression (Weber et al, 2018).…”
Section: Discussionmentioning
confidence: 65%
“…Not only did this patient report a 70% decrease in total pain score, but also a decrease in depressive symptoms. Due to the success of this treatment, the patient was retreated in the same manner when presenting again 5-months later ( Weber et al, 2018 ). The mitigation of depressive symptoms in pain conditions could potential serve as a niche application for ketamine in the future.…”
Section: Clinical Evidence Of Ketamine Efficacymentioning
confidence: 99%